Translation Errors of EFL Intern Students in a Professional Translation Company: A TQA-Based Analysis - Nabila, Putri; Eka Budiastuti, Riana; Deni Wijayatiningsih, Testiana (Jurnal Bahasa Inggris, 2026)
This study examines the types of English-Indonesian translation errors produced by intern students at Tap Indo Translation Company and identifies the challenges influencing these errors in a professional context. Employing a descriptive qualitative approach, the data were gathered from translated documents created by five interns, validation results from three professional assessors, and semi-structured interviews with the participants. The analysis applied the Translation Quality Assessment (TQA) framework by Nababan, Nuraeni, and Sumardiono (2012), focusing on accuracy, acceptability, and readability. The results indicate that readability achieved the highest mean score (2.67), suggesting that most translations were generally clear and easy to understand. Accuracy followed with a mean score of 2.60, showing that although some distortions in meaning and inconsistencies in terminology occurred, the main messages were largely conveyed. Meanwhile, acceptability received the lowest score (2.47), indicating that many translations lacked naturalness and did not fully align with Indonesian linguistic norms. Readability was supported by clear sentence structure and logical information flow, despite occasional complexity. Accuracy issues were mainly caused by misinterpretation of polysemous words and limited contextual awareness. Acceptability problems were reflected in literal translation tendencies and unnatural sentence constructions influenced by English syntax. Interview findings reveal that these challenges stem from limited familiarity with specialized terminology, lack of experience with professional text types, and time constraints. Nevertheless, the internship contributed to improving the interns’ translation awareness, decision-making abilities, and use of effective strategies such as revising drafts, consulting references, and seeking feedback.